Synthesis of Cu3P/SnO2 composites for degradation of tetracycline hydrochloride in wastewater. Issue 53 (12th November 2021) - Shi, Huancong; Zheng, Tao; Zuo, Yuanhui; Wu, Qiming; Zhang, Yun; Fan, Yi; Tontiwachwuthikul, Paitoon
Abstract : Cu3 P@SnO2 was synthesized with Cu3 P nanoparticles loaded on the surface of hollow SnO2 microspheres via a simple annealing process. Abstract : Antibiotic drugs have become dominating organic pollutants in water resources, and efficient removal of antibiotic drugs is the priority task to protect the water environment. Cu3 P/SnO2 photocatalysts of various Cu3 P loadings (10–40 wt% Cu3 P) were synthesized using a combination of hydrothermal synthesis and a partial annealing method. Their photocatalytic activity was tested for tetracycline hydrochloride (TC-HCl) degradation under visible light irradiation. Cu3 P/SnO2 samples were characterized by X-ray diffraction (XRD), N2 -adsorption, ultraviolet-visible diffuse reflectance spectra (UV-vis DRS), scanning electron microscopy (SEM) and electrochemical impedance spectroscopy (EIS). The results showed that the p–n type heterostructure between Cu3 P and SnO2 was successfully constructed, and addition of Cu3 P to SnO2 could improve its photocatalytic activity at an optimized loading of 30 wt% Cu3 P. In photocatalytic degradation studies, removal rates of around 80% were found in 30 minutes of dark reaction and 140 min of photodegradation. The removal rate was superior to that of Cu3 P and SnO2 alone under the same experimental conditions. According to trapping experiments and electron spin resonance (ESR) measurements, photogenerated holes (h + ) and superoxide radicals ˙O2 − were considered as the main oxidation species in the present system. Finally, the reuse experiments showed high stability of Cu3 P/SnO2 . This study reports Cu3 P as a cocatalyst combined with semiconductor SnO2 to form a highly efficient heterogeneous photocatalyst for the degradation of tetracycline hydrochloride for the first time.